Unrecognized severe obstructive sleep apnea as a dominant risk factor for non-arteritic anterior ischemic optic neuropathy in an apparently healthy patient - Katanić-Pasovski Katarina; Popević Martin; Pasovski Viktor; Petrović-Pajić Sanja; Iklozan Kristina; Rančić Nemanja; Resan Mirko; Raičević Ranko (Vojnosanitetski Pregled)
Introduction. Non-arteritic anterior ischemic optic neuropathy (NAION) is typically manifested by sudden, pain-less vision loss in one eye, often immediately upon waking up. The visual loss remains fairly stable over time but can be followed by similar manifestations in the fellow eye. One of the main causes for NAION is impaired hemodynamic regulation, followed by hypoperfusion of the optic nerve head. Recognized risk factors include arterial hyper-tension, hyperlipidemia, diabetes mellitus, smoking, etc. Case report. A 43-year-old man with a sudden painless right eye vision loss and typical symptoms and signs of NAION is presented. The ophthalmological examination, followed by fluorescein angiography and visual field testing, confirmed the diagnosis, while medical history had not revealed any of the standard risk factors. During hospitalization, the medical staff noted that the patient was snoring, waking up during the night while feeling short of breath, followed by excessive daytime sleepiness, which was later confirmed by family members as symptoms that had been present for several months. The patient was referred to a somnologist, who, after diagnostics, confirmed the presence of severe, untreated obstructive sleep apnea (OSA) and indicated treatment with a continuous positive air pressure (CPAP) device. The patient responded well to treatment, showing subjective and objective improvements in sleep quantity and quality. No progression of right eye NAION or vision impairments in the left eye has been noted after 6 months from diagnosis and CPAP introduction. Conclusion. OSA was probably the main underlying cause of NAION in this patient. We point out that OSA screening in high-risk patients can contribute to the early diagnosis and prevention of NAION.